2021
DOI: 10.3390/ijerph18168539
|View full text |Cite
|
Sign up to set email alerts
|

Women Suffered More Emotional and Life Distress than Men during the COVID-19 Pandemic: The Role of Pathogen Disgust Sensitivity

Abstract: The outbreak of the COVID-19 has brought upon unprecedented challenges to nearly all people around the globe. Yet, people may differ in their risks of social, economic, and health well-being. In this research, we take a gender-difference approach to examine whether and why women suffered greater emotional and life distress than men at the early stage of the COVID-19 outbreak in China. Using a large nationwide Chinese sample, we found that compared to men, women reported higher levels of anxiety and fear, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 47 publications
(52 reference statements)
4
19
0
1
Order By: Relevance
“…Such anxiety would further promote health-protective behavior (e.g., helping but social distancing) against social contact with high-risk of infection. This finding is consistent with evidence suggesting that PDS is associated with more severe stress and anxiety disorders [24,34], especially during disease outbreaks. For example, people with higher disgust proneness reported greater fear and anxiety during the 2009-2010 H1N1 "swine flu" [21,22], the 2014-2015 Ebola outbreaks [23], and the COVID-19 pandemic [35].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Such anxiety would further promote health-protective behavior (e.g., helping but social distancing) against social contact with high-risk of infection. This finding is consistent with evidence suggesting that PDS is associated with more severe stress and anxiety disorders [24,34], especially during disease outbreaks. For example, people with higher disgust proneness reported greater fear and anxiety during the 2009-2010 H1N1 "swine flu" [21,22], the 2014-2015 Ebola outbreaks [23], and the COVID-19 pandemic [35].…”
Section: Discussionsupporting
confidence: 92%
“…At the individual differences level, people who have stronger pathogen avoidance motives (e.g., high on pathogen disgust sensitivity) might experience more severe emotional distress during COVID-19 outbreaks and are more likely to avoid social contact than others. Consistent with this possibility, previous studies found that individuals who have higher sensitivity toward pathogen cues reported greater anxiety disorders during the H1N1 "swine flu" [21,22], the Ebola outbreaks [23], and the COVID-19 pandemic [24]. In addition to emotional distress, they also reported increased engagement in social distancing during the pandemic [4].…”
Section: Introductionmentioning
confidence: 58%
“…In the model quantifying predictors of emotional distress, female gender was strongly associated with distress, as well as the only demographic factor predictive of an increase in distress, compared to levels in spring 2019. This finding is consistent with a body of literature on gender discrepancies in anxiety and stress-related disorders [36], also evident during COVID-19 [37]. Relative to men, women have nearly twice the prevalence of generalised anxiety and panic disorder, as well as higher incidence and more severe symptoms of post-traumatic stress disorder after exposure to threatening events [38].…”
Section: Discussionsupporting
confidence: 89%
“…Compared to studies focusing on fear of infection, reports on sex differences in disgust sensitivity are fewer but their findings are anyway consistent with evolutionary predictions. Using a large nationwide Chinese sample, Ding, Yang, Ji, and Guo (2021) found that the COVID-19 outbreak increased levels of pathogen disgust sensitivity more in women than in men. In a large sample of Australian university students, Stevenson, Saluja, and Case (2021) found that the increase in disgust sensitivity observed during the COVID-19 pandemic was significantly greater in women than in men.…”
Section: Discussionmentioning
confidence: 99%